Barkhaa Barkhaa - A Shower of Happiness in a Child’s Life - A Shower of Happiness in a Child’s Life - Pandey, Lata (THE PRIMARY TEACHER, 2009)
The most wonderful and fascinating experiences of childhood are listening to stories and later on reading stories. Stories if used as a meaningful resource of learning can motivate children to learning to read. The stories not only provide enjoyment to the children, but also teach them many other things. Stories can also help in developing reading skills among children. Guessing something plays a very prominent role in the process of reading. Beginning from the first day of school, children must get ample opportunities to predict the text, when they learn to read. But in reality it does not happen frequently. In the initial classes at the primary level children are only taught to match letters with sounds. It is assumed that the children will gradually learn to read by establishing a link between letters and sounds. Even if children manage to pick up reading by joining letters, they still do not become successful readers. One reason for this failure is that we never pay sufficient attention to train children in the skill of prediction. If a child tries to read using her/his innate capacity to predict, she/he is discouraged. In this context an effort has been made in Barkhaa**– Graded Reading Series for children of Classes I and II to get plentiful opportunities of prediction while reading the stories. Barkhaa is a pedagogical tool which will help the children of Classes I and II in learning reading and to arouse in them the urge to read more and more